The effect of risk disclosure on the cost of equity capital and firm value (An empirical study of manufacturing companies listed on the Indonesia Stock Exchange period 2015-2017) - Eka Sri Sumardani; Rr Sri Handayani (Universitas Hayam Wuruk Perbanas, 2019)
This study examines the effect of corporate risk disclosure on cost of equity capital and firm value. It uses the ratio of market value to book value, the ratio of leverage, consumer price index, growth, firm size, independent audit committee, and net profit during the study period and net profit in the previous year as control variables. The population consists of all manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 - 2017. The sample was taken using a purposive sampling method, with the total sample of 99 companies. The data were analyzed using multiple regression analysis to test the hypothesis. The results indicate that corporate risk disclosure has a negative effect on the cost of equity capital but corporate risk disclosure has a positive effect on firm value.